Analisis Visi Dan Konsep Pendidikan Karakter Di Persekolahan Dan Di Perguruan Tinggi Dalam Membentuk Karakter Unggul Generasi Muda - Agil Nanggala; Dianni Risda (Jurnal Civic Hukum, 2023)
Character education is so important to teach in schools and in universities, because it relates to civic virtue, character education is a vehicle for transforming the values ​​of Pancasila and the 1945 Constitution to the younger generation, this research aims to analyze substance, realization, policy support , obstacles are also the potential of character education in schools and in tertiary institutions, because it is mandated through the constitution, government regulations, and curriculum, so that all schools and tertiary institutions are required to carry out character education to form superior or Pancasilaist character of the younger generation. This research was conducted through a qualitative approach with the method of literature study, data analysis was: reduction, display and verification. Research results: 1) the application of character education in schools is emphasized by the Merdeka Curriculum 2022, through the Pancasila student profile program, which contains the values ​​of divinity, humanity, unity, creativity, critical thinking, and self-reliance, is closely related to character education, the model of character education in schools are: autonomy, integration, extracurricular, and collaboration, the goals of character education need to become the vision of the institution, so that the curricular and instructional goals of each subject in schooling accommodate strengthening the character of students, to overcome obstacles and challenges of character education, schools need to consistently innovate on the curriculum and learning, strengthening teacher qualifications, optimizing extracurriculars, optimizing technology, information and communication, and increasing students' attention, 2) character education policies in tertiary institutions, are heavily influenced by university autonomy, because they are authorized to compile and develop curricula on character education, realization of character education in tertiary institutions, can be through MKWK, special courses, student activity units, service learning models, as well as student character development activities, to overcome obstacles as well as challenges to character education, tertiary institutions need to: develop science and knowledge, innovate in curriculum and learning, strengthening lecturer qualifications, optimizing technology, information and communication, and realizing pentahelix collaboration. The conclusion of the research is that the existence of character education in schools and in tertiary institutions accommodates the vision of forming a superior young generation, supported by the concept of character education which is holistic and integrative, but must be accompanied by commitment, consistency and exemplary of each party.